2013
DOI: 10.1007/s00299-013-1508-0
|View full text |Cite
|
Sign up to set email alerts
|

Signaling molecules and cell death in Melissa officinalis plants exposed to ozone

Abstract: The study focuses on the interaction between reactive oxygen species and hormones that regulate the programmed cell death in plants of Melissa officinalis exposed to ozone. Interaction between hormone and redox signaling pathways has been investigated in ozone-stressed (200 ppb, 5 h) lemon balm to verify if the response resembles the biotic defense reactions. In comparison to controls, plants exhibited foliar injury and the cell death was induced by (1) biphasic production of hydrogen peroxide and superoxide r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
44
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 34 publications
(48 citation statements)
references
References 84 publications
4
44
0
Order By: Relevance
“…riken.jp) on ABA content despite its recent role in controlling ET evolution in response to O 3 . ABA content was enhanced in O 3 -fumigated Melissa officinalis plants (200 ppb, 5 h) preceding the secondary ROS production peak (Pellegrini et al 2013). However, in some species, O 3 has no effect on its endogenous content (Döring et al 2014).…”
Section: Abscisic Acid (Aba)mentioning
confidence: 96%
See 4 more Smart Citations
“…riken.jp) on ABA content despite its recent role in controlling ET evolution in response to O 3 . ABA content was enhanced in O 3 -fumigated Melissa officinalis plants (200 ppb, 5 h) preceding the secondary ROS production peak (Pellegrini et al 2013). However, in some species, O 3 has no effect on its endogenous content (Döring et al 2014).…”
Section: Abscisic Acid (Aba)mentioning
confidence: 96%
“…At a functional level, some experiments provide evidence that the SA perception amplifies downstream signals that lead to the cell death in a process similar to what occurs during plant-pathogen interactions (Tamaoki 2008). Pellegrini et al (2013) reported that O 3 triggers marked increases in SA (conjugated and free forms) in asymptomatic leaves of M. officinalis after 8 h from the beginning of exposure. In this case, SA may have a role in the upregulation of antioxidative systems during the lesion spread (as confirmed by the increase of ascorbate and glutathione content).…”
Section: Salicylic Acid (Sa)mentioning
confidence: 97%
See 3 more Smart Citations